P62/SQSTM1 is required for cell survival of apoptosis‐resistant bone metastatic prostate cancer cell lines. Issue 2 (30th September 2013) - Chang, Megan A.; Morgado, Micaela; Warren, Curtis R.; Hinton, Cimona V.; Farach‐Carson, Mary C.; Delk, Nikki A.
Abstract BACKGROUND Bone marrow stromal cell (BMSC) paracrine factor(s) can induce apoptosis in bone metastatic prostate cancer (PCa) cell lines. However, the PCa cells that escape BMSC‐induced apoptosis can upregulate cytoprotective autophagy. METHODS C4‐2, C4‐2B, MDA PCa 2a, MDA PCa 2b, VCaP, PC3, or DU145 PCa cell lines were grown in BMSC conditioned medium and analyzed for mRNA and/or protein accumulation of p62 (also known as sequestome‐1/SQSTM1), Microtubule‐associated protein 1 light chain 3B (LC3B), or lysosomal‐associated membrane protein 1 (LAMP1) using quantitative polymerase chain reaction (QPCR), Western blot, or immunofluorescence. Small interfering RNA (siRNA) was used to determine if p62 is necessary PCa cell survival. RESULTS BMSC paracrine signaling upregulated p62 mRNA and protein in a subset of the PCa cell lines. The PCa cell lines that were insensitive to BMSC‐induced apoptosis and autophagy induction had elevated basal p62 mRNA and protein. In the BMSC‐insensitive PCa cell lines, siRNA knockdown of p62 was cytotoxic and immunostaining showed peri‐nuclear clustering of autolysosomes. However, in the BMSC‐sensitive PCa cell lines, p62 siRNA knockdown was not appreciably cytotoxic and did not affect autolysosome subcellular localization. CONCLUSIONS A pattern emerges wherein the BMSC‐sensitive PCa cell lines are known to be osteoblastic and express the androgen receptor, while the BMSC‐insensitive PCa cell lines are characteristically osteolytic and do not express the androgen receptor. Furthermore, BMSC‐insensitive PCa may have evolved a dependency on p62 for cell survival that could be exploited to target and kill these apoptosis‐resistant PCa cells in the bone. Prostate 74:149–163, 2014. © 2013 Wiley Periodicals, Inc.